KUALITAS PELAYANAN PARKIR BERLANGGANAN DI KOTA PASURUAN - Ardian Bagus Setiawan; Agus Widiyarta (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2022)
Retribution is a regional levy as payment for services or the granting of certain permits specifically provided or granted by the Regional Government for the benefit of individuals or entities. In a retribution there are services provided by the government. The services provided by the government or often called public services are not all running well. This article aims to explain the quality of subscription parking services in Pasuruan City from the aspect of public services. This research is important to do because there are many complaints from the public as service users regarding the services provided by the subscription parking operator. This study will focus on analyzing respondents' responses to the dimensions of public services which are divided into responsiveness, responsibility, and accountability. The method used in this research is a quantitative approach with descriptive research type survey research category. Respondents in this study amounted to 100 people who are users of subscription parking services in Pasuruan City. In this study using simple random sampling as a sampling technique. The results show that the quality of subscription parking services in Pasuruan City gets a score of 74.6% or is included in the good category.